Lettere a Oreste Macrí Schedatura e regesto di un fondo, con un'appendice di testi epistolari inediti - Collini, Dario (Biblioteca di Studi di Filologia Moderna, 2018)
This book edited by Dario Collini is a collection of the work by several young researchers (belonging to the University of Florence's research groups "GREM" and "NGEM"), who have studied the 17,000 letters belonging to the of the Macrì Association under Anna Dolfi's guidance. The aim of this book is to offer an extraordinary work tool to those who are interested in Hermeticism, literary criticism and poetry of the 20th century in Italy. The flashes coming from these letters, be them shadows from the bottom or "intermittent lights", are signs of the human genesis of culture, because they retain traces of what is linked to everyday life, and contributes to the construction of the '"great" history and of the intellectual and political planning alongside it. Therefore readings, books, magazines, collaborations, friendships, resentments, travels, literary and private passions emerge from these documents, so as to give voice to an era and its protagonists.